The quasi-deterministic limit of population dynamics - Aparicio, Juan Pablo (2012)
We discuss and compare different, but related, approximations to the stochastic dynamics of populations, all of them having as limit the same deterministic dynamics. The diffusion approximation,linearized diffusion approximation and the Poisson approximation are briefly revisited and their quality as approximations for large, but given, populations is addressed analytically as well as with demonstrative examples.